Large contrast enhancement by sonication assisted cold development process for low dose and ultrahigh resolution patterning on ZEP520A positive tone resist - Tobing, Landobasa Yosef Mario A. L. (2013)
The authors demonstrate a robust, low dose, high contrast, and ultrahigh resolution patterning process based on sonication assisted development of ZEP520A positive tone resist in both room and cold temperature. The contrast as high as γ ∼ 25 and γ ∼ 9.14 can readily be achieved in 6 °C and room temperature development, respectively, in diluted n-amyl acetate solution. The high contrast is demonstrated on 90 nm thick ZEP resist at 20 kV acceleration voltage, from which 20 nm thick titanium lift-off of 60 nm pitch lines and 50 nm pitch dots can be successfully achieved.